2018
DOI: 10.1590/1678-5150-pvb-5433
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal B-mode and Doppler ultrasonography of chemically restrained agouti (Dasyprocta prymnolopha Wagler, 1831)

Abstract: Agoutis are small-sized wild animals whose body weight can reach up to 4kg, and are found throughout Brazil. They are considered important seed dispersers, especially for big trees and there are species that rely almost exclusively on these animals for their territorial distribution. The objective of the present study was B scan and Doppler ultrasound characterization of the abdominal organs of healthy agoutis reared in captivity. Fifteen agoutis, chemically restrained, were used from the Nucleus for Wild Anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The current investigation reported that, the renal cortex echogenicity was similar to or slightly less than the hepatic parenchyma which came on the same line with findings of Moarabiet al (2011) in New Zealand white rabbit and Tolai Hare and Dimitrov (2012), Redrobe (2013) and Banzato et al (2014a) in rabbit. WhileBanzato et al (2014b in rat and Pessoa et al (2018) in Agoutis demonstrated that, the renal cortex was more in echogenicity than the liver parenchyma.…”
Section: Discussionmentioning
confidence: 95%
“…The current investigation reported that, the renal cortex echogenicity was similar to or slightly less than the hepatic parenchyma which came on the same line with findings of Moarabiet al (2011) in New Zealand white rabbit and Tolai Hare and Dimitrov (2012), Redrobe (2013) and Banzato et al (2014a) in rabbit. WhileBanzato et al (2014b in rat and Pessoa et al (2018) in Agoutis demonstrated that, the renal cortex was more in echogenicity than the liver parenchyma.…”
Section: Discussionmentioning
confidence: 95%
“…As protocol was followed the methodology described by Pessoa et al [10], using a combination of ketamine hydrochloride 1 (40 mg/kg) and xylazina hydrochloride 2 (1 mg/kg), intramuscularly. The action of the drugs occurred about 10 min after application, and lasted 30 to 40 min, with no need for reapplication or complications.…”
Section: Chemical Containmentmentioning
confidence: 99%